Labyrinth of stars - Liu, Marjorie M. (Liu, Marjorie M. Hunter Kiss novel., 2014)
After the Aetar nearly kill Maxine's unborn child, and a betrayal within her own ranks leaves Maxine's husband, Grant, poisoned and dying, Maxine is forced to attack a race of beings that possesses almost unlimited power. Doing so will require she make a deal with the devil,the devil that lives inside her, risking both her sanity and her soul as she slowly transforms into something more than human. But even that might not be enough to save Grant, because the very thing that Maxine is becoming is destined to destroy the world